Rational Design of a Chimeric Derivative of PcrV as a Subunit Vaccine Against Pseudomonas aeruginosa - Wan, Chuang; Zhang, Jin; Zhao, Liqun; Cheng, Xin; Gao, Chen; Wang, Ying; Xu, Wanting; Zou, Quanming; Gu, Jiang (Frontiers in Immunology, 2019)
Pseudomonas aeruginosa (PA) is a major cause of nosocomial infections, which remain an unsolved problem in the clinic despite conventional antibiotic treatment. A PA vaccine could be both an effective and economical strategy to address this issue. Many studies have shown that PcrV, a structural protein of the type 3 secretion system (T3SS) from PA, is an ideal target for immune prevention and therapy. However, difficulties in the production of high-quality PcrV likely hinder its further application in the vaccine industry. Thus, we hypothesized that an optimized PcrV derivative with a rational design could be produced. In this study, the full-length PcrV was divided into four domains with the guidance of its structure, and the Nter domain (Met1-Lys127) and H12 domain (Leu251 - Ile294) were found to be immunodominant. Subsequently, Nter and H12 were combined with a flexible linker to generate an artificial PcrV derivative (PcrVNH). PcrVNH was successfully produced in E. coli and behaved as a homogenous monomer. Moreover, immunization with PcrVNH elicited a multifactorial immune response and conferred broad protection in an acute PA pneumonia model and was equally effective to full-length PcrV. In addition, passive immunization with anti-PcrVNH antibodies alone also showed significant protection, at least based on inhibition of the T3SS and mediation of opsonophagocytic killing activities. These results provide an additional example for the rational design of antigens and suggest that PcrVNH is a promising vaccine candidate for the control of PA infection.